Hukum Waris Perspektif Hukum Perdata (Burgerlijk Wetboek) - Maryam Qurotul Aini, Siti; Millati, Etik Nur (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
Basically inheritance is a transfer of all rights and duties of a deceased person to his heirs. The definition of inheritance law is a law that regulates the transfer of wealth left by someone who died and the consequences for his heirs. Inheritance is divided into two, namely Inheritance under the law, also called the inheritance of ab-intestato and testamentair inheritance, namely inheritance based on a testament or testament according to Burgerlijk Wetboek.